Lernaea cyprinacea trinity assembly - Porter, Megan L.; Steck, Mireille; Roncalli, Vittoria; Lenz, Petra H. (Dryad Digital Repository, 2017)
Trinity assembly file with all contigs from reassembled Lernaea cyprinacea RNA-seq data.